2019
DOI: 10.29333/ejgm/93472
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ethical climate of hospital and moral courage of nursing staff

Abstract: Introduction:Courage is the ethical virtues that has special place in the nursing profession, whose role in patient support is highlighted. Courage virtues seems to grow with environmental reinforcement and social support. Hospital as a dynamic social institution has different forms of ethical climates. The purpose of this study was to determine the correlation between the ethical climate of the hospital and the moral courage of the nurses in one of the medical universities of Iran medical science's selected h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 14 publications
2
12
0
3
Order By: Relevance
“…It is essential therefore, to have moral courage as a strategy to reinforce ethics and doing courageous deeds in nursing care (Bickhoff et al, 2017;Hawkins et al, 2014). Studies have shown that as ethical doers, nurses need moral courage to manage ethical challenges, honor professional commitment to patients, and work based on ethical codes (Taraz Z et al, 2019) The concept of moral courage was introduced during Florence Nightingale era and among all personal merits and speci cations, the principle of nursing is benevolence (Numminen et al, 2018).This characteristic allows an individual to act ethically (Yeom et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential therefore, to have moral courage as a strategy to reinforce ethics and doing courageous deeds in nursing care (Bickhoff et al, 2017;Hawkins et al, 2014). Studies have shown that as ethical doers, nurses need moral courage to manage ethical challenges, honor professional commitment to patients, and work based on ethical codes (Taraz Z et al, 2019) The concept of moral courage was introduced during Florence Nightingale era and among all personal merits and speci cations, the principle of nursing is benevolence (Numminen et al, 2018).This characteristic allows an individual to act ethically (Yeom et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ethical climate is a sort of organizational climate and as a part of organization character, represents ethics in the organization (Cerit B et al, 2019; Dzeng et al, 2018).Ethical standards in organization promote respect and honesty among personnel and increase job satisfaction and organizational success (Süreci, 2015).Moreover, ethical climate enhances motivation in employees, improves organizational commitment, and preserve personnel(Suhonen et al, 2011).It also creates a sense of ownership and attenuates loneliness in employees, which in return adds to the performance of organization(Eroğluer K et al, 2015).On the other hand, improper ethical climate is a factor in understaffed wards, loss of motivation, and job dissatisfaction in nurses(Suhonen et al, 2011). Studies in Iran have shown that nurses' perception of ethical climate in hospital was at moderate level(Taraz Z et al, 2019).And limited studies have been conducted in nursing to examine the severity of this relationship and the simultaneous effect of variables and its causal relationship.…”
mentioning
confidence: 99%
“…Do total de artigos, 25% (n=3) (Pauly, et al, 2009;Huang, et al, 2012;Asgari, et al, 2019) verificaram associações significativas (p<0,05) do clima ético com satisfação no trabalho, comportamento organizacional e sofrimento moral. Os outros artigos, que correspondiam a 75% (n=9) (Taraz, et al, 2019;Silén, et al, 2011;Hwang & Park, 2014;Borhani, et al, 2014;Numminen, 2018;Dinc & Huric, 2017;Hashish, 2017;Jang & Oh, 2017;Ozden, et al, 2019. por As correlações variaram de 0,1(A8) a 0,90 (A11), em que 88,9% (n=8) foram classificadas como positivas entre os fatores relacionados ao trabalho e variável clima ético.…”
Section: Resultsunclassified
“…Portanto, é necessário que a gestão hospitalar, assim como toda a equipe esteja envolvida no processo do cuidado, mostrando o quão importante é a maneira de lidar com os pacientes que buscam ajuda profissional. Dessa forma, relacionar e abordar questões éticas possibilita a compreensão de informações gerais, que por vezes são aplicadas nas ações do clima ético que tende a ser positivo (Taraz, et al, 2019).…”
Section: Resultsunclassified
See 1 more Smart Citation